ANALYSIS OF AUDIT DELAY DETERMINANTS IN TECHNOLOGY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Zufrizal (CV. Radja Publika, 2021)
This research analyzes the determinants of audit delay in technology companies listed on the Indonesia Stock Exchange for the period 2016-2020. The study aims to identify the factors that contribute to audit delay and to provide insights for companies, auditors, and regulators in improving the efficiency of the audit process. The data used in this study were obtained from the financial statements and annual reports of 27 technology companies listed on the Indonesia Stock Exchange. The results of the study indicate that the size of the company, complexity of the company's operations, auditor reputation, and financial distress significantly affect audit delay. The findings suggest that larger companies with complex operations, lower auditor reputation, and financial distress experience longer audit delay. The study also highlights the importance of auditor reputation in reducing audit delay. The implications of these findings for companies, auditors, and regulators are discussed.